Pemanfaatan Air Tanah Untuk Pertanian Di Kecamatan Delanggu Kabupaten Klaten - Nugroho, Wahyu Tri, Drs. Munawar Cholil, M.Si, Dr. Ir. Imam Hardjono, M.Si (2016)
This research has the title of Ground Water Utilization for Agricultural In Subdistrict Delanggu District Klaten. This research has a goal 1) Determine the total volume of groundwater used for agricultural land in the district Delanggu. 2) Knowing distribution factor use of groundwater and spread wells drill for agricultural land in the district Delanggu. The method used this research is direct observation and data collection in the field or survey methods. Sampling in this research technique stratified random sample (stratified). Data analysis in this research form the primary data and secondary data. Primary data is data spread wells drill, interviews with farmers about the use of wells drill and water discharge measurements wells drill. While the secondary data in the form of rainfall data in the study area, the data of land resources in the study area, and a map of agricultural land resources. Results obtained from the analysis of this data in the form of the use of water wells drilled by strata land units. The study area has 8 types of land units, namely V7 I Rk Pm, I Rk Sw V7, V7 I Rk Tg, I Rk L V7, V8 II Rk Pm, V8 II Sw Rk, Rk Tg II V8, V8 II Rk L. based fieldwork, the study area has 60 buildings wells drill which only spread on land units I V7 and V8 II Rk Rk Sw Sw. The use amount of the volume of ground water through wells drill are as follows: 1) on land units V7 I Rk Sw is an average of 3.470.753,19,19 liters / ha / planting time. 2) on land units V8 II Rk Sw is an average of 4,581,424.88 liters / ha / planting time. Results of this research form Distribution factor Map Use of Groundwater In Sub Delanggu in year 2015 at a scale of 1: 40,000.